Recent trends and patterns in HIV‐1 transmitted drug resistance in the United Kingdom. Issue 3 (1st August 2016) - Tostevin, A; White, E; Dunn, D; Croxford, S; Delpech, V; Williams, I; Asboe, D; Pozniak, A; Churchill, D; Geretti, AM; Pillay, D; Sabin, C; et al.
Abstract : Objectives: Transmission of drug‐resistant HIV‐1 has decreased in the UK since the early 2000s. This analysis reports recent trends and characteristics of transmitted drug resistance (TDR) in the UK from 2010 to 2013. Methods: Resistance tests conducted in antiretroviral treatment (ART)‐naïve individuals between 2010 and 2013 were analysed for the presence of transmitted drug resistance mutations (TDRMs), defined as any mutations from a modified 2009 World Health Organization surveillance list, or a modified 2013 International Antiviral Society‐USA list for integrase tests. Logistic regression was used to examine associations between demographics and the prevalence of TDRMs. Results: TDRMs were observed in 1223 (7.5%) of 16 425 individuals; prevalence declined from 8.1% in 2010 to 6.6% in 2013 ( P = 0.02). The prevalence of TDRMs was higher among men who have sex with men (MSM) compared with heterosexual men and women (8.7% versus 6.4%, respectively) with a trend for decreasing TDRMs among MSM ( P = 0.008) driven by a reduction in nucleoside reverse transcriptase inhibitor (NRTI)‐related mutations. The most frequently detected TDRMs were K103N (2.2%), T215 revertants (1.6%), M41L (0.9%) and L90M (0.7%). Predicted phenotypic resistance to first‐line ART was highest to the nonnucleoside reverse transcriptase inhibitors (NNRTIs) rilpivirine and efavirenz (6.2% and 3.4%, respectively) but minimal to NRTIs, including tenofovir, and protease inhibitors (PIs). No major integrase TDRMs were detected among 101 individuals tested while ART‐naïve. Conclusions: We observed a decrease in TDRMs in recent years. However, this was confined to the MSM population and rates remained stable in those with heterosexually acquired HIV infection. Resistance to currently recommended first‐line ART, including integrase inhibitors, remained reassuringly low.